(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
This research aims to address the challenge of comprehending swimming material, which students at SMP Negeri 7 Pati find to be difficult. This difficulty arises from the complexity of the process. The process cannot be understood solely through books or worksheets. Additionally, there is a lack of optimized learning strategies and in-depth material on the techniques. The study utilized a quantitative approach with a quasi-experimental design involving 34 students from class VIII H, divided into two groups for pretest-posttest control. The research instrument contained evaluations on affective, cognitive, and psychomotor aspects of breaststroke swimming. Data analysis was conducted using the paired sample T test. The research results, analyzed with IBM SPSS 23, indicated that the experimental group had a statistically significant difference. (2-tailed) = 0.000, indicating p < 0.05, showing a significant 47% increase in learning outcomes in breaststroke swimming material. As a result, Ho1 is rejected and Ha1 is accepted. The control group exhibited a significant level in comparison. (2-tailed) = 0.789, with p > 0.05, indicating a lack of significant increase in learning outcomes. Thus, Ho1 is accepted and Ha1 is rejected. In conclusion, the Si Juara application has positively impacted breaststroke swimming learning outcomes at SMP N 7 Pati, resulting in a notable improvement. Future researchers should focus on enhancing learning models to optimize learning results